Case report: Cases of narcolepsy misdiagnosed as other psychiatric disorders - Shen, Zhongxia; Shuai, Yibin; Mou, Shaoqi; Shen, Yue; Shen, Xinhua; Yang, Shengliang (Frontiers in Psychiatry, 2022)
Narcolepsy is characterized by uncontrollable excessive daytime sleepiness (EDS), paroxysmal cataplexy, sleep paralysis (SP), hallucinations before falling asleep or upon awakening, which is often misdiagnosed as psychiatric disorders such as depression and schizophrenia resulting from the overlap in symptoms and the lack of understanding of narcolepsy. Three narcolepsy cases misdiagnosed as depression, dissociative disorders and schizophrenia were analyzed to highlights the high occurrence of the misdiagnosis of narcolepsy in clinical practice, the main reasons for this dilemma attributes to the lack of adequate sleep medicine education as well as professional technicians. MDT(multi-disciplinary team) which composed with psychiatrists and sleep specialists should be established to deal this problem.